Analyzing the Self-Organized Evolution of Informal Spaces in Urban Villages: Reflections from Shenxiang Village in Suzhou - Cheng Jie; Li Haoze; Wang Yong (Redai dili, 2023)
Informal spaces in urban villages represent a spatial chimera of socio-economic activities arising from driving social demands. Investigating the evolution and inherent rules of such spaces can provide direction and strategies for good governance. This study analyzes the process and outcomes of the self-organized evolution of informal spaces by considering their self-organizational characteristics. Herein, the Shenxiang village, which is a typical mature urban village in Suzhou, was considered as an example. We adopted qualitative research methods, such as questionnaire surveys and semi-structured interviews. The agglomeration and formation of informal spaces in Shenxiang is the consequence of self-organized evolution. This can be attributed to the interaction of internal and external environments, which is influenced by the socio-cultural concepts of local villagers and relationships among external groups. Based on the main body of spatial organization, the self-organized evolution of informal spaces in urban villages was divided into the following stages: "individual-oriented self-creation," "relationship-oriented self-expansion," and "social capital-oriented self-evolution." Furthermore, the spatio-temporal characteristics and self-organizational-evolution mechanisms of these informal spaces were analyzed at each stage. The findings are as follows: (1) During the evolution of informal spaces, the main body of spatial organization expands from "village people" to "rural people" and "insiders." This is the consequence of self-organized evolution between villagers and alien groups. In urban villages, the evolution and reconstruction of informal spaces is caused by the expansion and variation in social relations. (2) During the self-organization and evolution of informal spaces, the relationship network is crucial in strengthening trust and building consensus, spanning blood relationships in the "self-creation" stage and geographical and industrial relationships in the "self-evolution" stage. The informal spatial self-organization of urban villages relies on the sub-social structure constructed by the original relationship network, which perpetuates the consensual regional culture, conceptual consciousness, and living habits, and enhances the cohesiveness and centripetal force of self-organization. This study aimed to gain deeper insights into informal spaces in urban villages, formulate a theoretical framework for their governance, and analyze the order and rules of internal self-organization. We believe that such informal spaces are self-balanced and relatively independent informal economies that facilitate a symbiotic relationship between local villagers and external groups. The transformation and optimization of informal spaces in urban villages is a potential challenge. The guiding approach for optimization promotes the following: forming informal space communities in urban villages, respecting and stimulating their self-organization order, adhering to the mutual unity principle of self-organization and external organizations, combining the external impetus and internal development capabilities of the system, and adopting bottom-up consultation actions to balance the group interest more efficiently. To promote the governance of informal spaces in urban villages, it is crucial to adhere to the logic and rules of their self-organization.